Capital Utilization, Productivity, and Output Gap - You, Jong Keun (The Review of Economics and Statistics, 1979)
T HE rate of aggregate output a nation's economy can produce under the conditions of full employment depends on, among other things, the available man-hours, capital stock, and technology. Previous studies on the output gap and potential output, however, have not directly introduced into their models underutilization of capital input caused by the fluctuations of demand. To cite a few of the more important studies, Okun's (1962) work was launched exclusively from the labor standpoint with no regard given to the contribution the underutilization of Capital made to the output gap. The entire output gap was measured and analyzed in conjunction with the unemployment rate. Other studies that have introduced more sophisticated models of cyclical fluctuations have again tended to emphasize the role which the labor force plays. For example, the works of Thurow and Taylor (1966), Kuh (1966), Friedman and Wachter (1974), and Perry (1971 and 1977) have aimed at elaborate estimates of labor force participation rate, average hours of work, and productivity in order to analyze the component parts of potential output, however, clouding in the process the underutilization of capital. In other words, although the underutilization of capital is indirectly accounted for in these models, numerical weights cannot be placed upon that part of the output gap generated by the underutilization of capital. In this paper we attempt to decompose the output gap in order to estimate cyclical fluctuations of inputs and their contributions to the output gap, while preserving the simplicity of Okun's Law. Our hypothesized relationship between the output gap and employment rate is the same as Okun's elasticity specification, but a more precise specification of potential and actual output is made by the use of an aggregate production function. The use of aggregate production function and additional hypotheses on the behavior of the capital utilization rate and man-hours enables us to estimate the input gap as well as the output gap. The decomposition of the output gap proved to be helpful in explaining cyclical variations of labor productivity.